Hypodematium guilinense, sp. Nov. – a new fern species From China (Bangladesh Journal of Botany, 2023)
Hypodematium guilinense J. X. Li & X. J. Li, sp. nov. of Hypodematium Kunze belonging to Hypodematiaceae from Guangxi Zhuang Autonomous Region, China is described and illustrated. It is closer to H. crenatum (Forssk.) Kuhn & Decken but differs for its height (25-28 cm), narrowly triangular lamina, hairy (acicular) stipe, glabrous fronds (both abaxial and adaxial) and hairy (acicular) indusia. Comparative characters of these two closely related species are discussed, and both LM and SEM structures of spores and fronds are provided.Bangladesh J. Bot. 52(2): 595-599, 2023 (June) Special